A one-step real-time multiplex PCR for screening Y-chromosomal microdeletions without downstream amplicon size analysis. - Viviana Kozina; Heike Cappallo-Obermann; Jörg Gromoll; Andrej-Nikolai Spiess (PLoS ONE, 2011)
Y-chromosomal microdeletions (YCMD) are one of the major genetic causes for non-obstructive azoospermia. Genetic testing for YCMD by multiplex polymerase chain reaction (PCR) is an established method for quick and robust screening of deletions in the AZF regions of the Y-chromosome. Multiplex PCRs have the advantage of including a control gene in every reaction and significantly reducing the number of reactions needed to screen the relevant genomic markers.The widely established "EAA/EMQN best practice guidelines for molecular diagnosis of Y-chromosomal microdeletions (2004)" were used as a basis for designing a real-time multiplex PCR system, in which the YCMD can simply be identified by their melting points. For this reason, some AZF primers were substituted by primers for regions in their genomic proximity, and the ZFX/ZFY control primer was exchanged by the AMELX/AMELY control primer. Furthermore, we substituted the classical SybrGreen I dye by the novel and high-performing DNA-binding dye EvaGreen™ and put substantial effort in titrating the primer combinations in respect to optimal melting peak separation and peak size.With these changes, we were able to develop a platform-independent and robust real-time based multiplex PCR, which makes the need for amplicon identification by electrophoretic sizing expendable. By using an open-source system for real-time PCR analysis, we further demonstrate the applicability of automated melting point and YCMD detection.